Optimization of Sintering Time and Holding Time for 3D Printing of Fe-Based Metallic Glasses - Wenzheng Wu; Wei Liu; Haidong Du; Bofan Wang; Guiwei Li; Bin Sun; Shuo Zhang; Ji Zhao (Metals, 2018)
Fe-based metallic glasses are amorphous alloys with high strength, high hardness, and excellent corrosion resistance; however, the immaturity of processing methods has prevented their wide application in industrial production. Fe-based metallic glass parts were manufactured employing pneumatic injection additive manufacturing in this study. An evenly dispersed and stable Fe-based metallic glass powder slurry with a solids content of 50% was prepared firstly. Then the Fe-based metallic glass parts were printed. The printed parts were dried, debinded, and sintered for strengthening. The deformations of the printed parts and sintered parts relative to the original model were then analyzed by a 3D scanning reconstruction method. The slightly average bulging and sunken deformation of the printed parts and sintered parts confirmed the good printing accuracy of the pneumatic injection manufacture system. The effects of the sintering temperature and holding time on the properties of the sintered parts were studied. For a sintering temperature of 580 °C and holding time of 1 h, the surface quality of the sintered parts was better. The sintering of 3D-printed Fe-based metallic glass parts was preliminarily realized in this study, and the feasibility of preparing Fe-based metallic glass using pneumatic injection additive manufacture was verified.